A Systematic Study of Coumarin-Tetrazine Light-Up Probes for Bioorthogonal Fluorescence Imaging - Galeta, Juraj; Dzijak, Rastislav; Obořil, Jan; Dračínský, Martin; Vrabel, Milan (Chemistry (Weinheim an der Bergstrasse, Germany), 2020)
Fluorescent probes that light-up upon reaction with complementary bioorthogonal reagents are superior tools for no-wash fluorogenic bioimaging applications. In this work, a thorough study is presented on a set of seventeen structurally diverse coumarin-tetrazine probes that produce fluorescent dyes with exceptional turn-on ratios when reacted with trans-cyclooctene (TCO) and bicyclononyne (BCN) dienophiles. In general, formation of the fully aromatic pyridazine-containing dyes resulting from the reaction with BCN was found superior in terms of fluorogenicity. However, evaluation of the probes in cellular imaging experiments revealed that other factors, such as reaction kinetics and good cell permeability, prevail over the fluorescence turn-on properties. The best compound identified in this study showed excellent performance in live cell-labeling experiments and enabled no-wash fluorogenic imaging on a timescale of seconds.
Keywords: Fluorescent Dyes; Cell Line, Tumor; konfokální mikroskopie; optické zobrazování; Coumarins; tetrazines; Heterocyclic Compounds; Microscopy, Confocal; heterocyklické sloučeniny; click chemistry; lidé; Humans; Optical Imaging; live cell bioimaging; fluorescenční barviva; coumarins; kumariny; nádorové buněčné linie; fluorescence